The perceptions of four school principals in Chile about their impact on student outcomes and opportunities: a phenomenological study - Gilbert-Sáez, Monica F. (2020)
This thesis is a study of four school principals in Chile. It is a qualitative, phenomenological exploration of the experiences of these principals, how they may affect student outcomes and opportunities and the ways in which this might contribute to the lives of young people.